Nurdaya Craft Shop (Online Store) - HARUN, MUHAMMAD HAQIMI; Nur Liyana Sulaiman (Applied Information Technology And Computer Science, 2025)
This project addresses the imperative need for Nurdaya Craft, a Malaysian handcrafted and gift items firm, to establish a robust online presence through the development of an e-commerce platform. The challenge was an inefficient order process due to reliance on WhatsApp, which affected effective communication and customer incentives. The objectives are to design Nurdaya Craft Shop Online Store System (NCS Online Store) based on object oriented approach, to develop a web based of NCS Online Store System and also to test using alpha and beta testing on NCS Online Store System. Utilizing a Prototyping methodology, Figma and Visual Studio were employed in the respective phases to enhance the efficiency and effectiveness of the overall process. The project will improve order management by replacing the inefficient manual order tracking with streamlined digital process, and future work includes integrating advanced analytics and reporting tools to help managing operations and identify growth opportunities.